Sacrifice and Tribute in Hosea 6:6: The Implication of Contextual Worshipping - Susila, Tirta (International Journal Labs, 2022)
Hosea was not the only prophet who saw and criticized the falsehood of the Israelites' worship as God's people. Hosea's specialty, however, is that in his preaching he repeatedly puts forward, and therefore, reflects a fairly detailed theological concept of understanding the true, meaningful, and proper worship of God's people. In his preaching, Hosea highlighted two things in connection with Israel's worship, namely between the